KEPUASAN PASIEN RAWAT JALAN DI POLI KANDUNGAN RUMAH SAKIT KHUSUS DAERAH IBU DAN ANAK PERTIWI MAKASSAR - Asmirati Yakob; Najmi Kamariah; Muttaqin (Jurnal Midwifery, 2022)
Intoduction Satisfaction upon hospital services is among the main factors of service quality from a hospital. The Failure and success status of hospital services are determined by patient satisfaction in which paient is the consumer of hospital. The Rumah Sakit Khusus Daerah (RSKD) Ibu and Anak Pertiwi has become one of the most visited hospitals in Makassar City and It provides various services for them who needed health care. This study aimed to investigate and reveal the satisfaction of outpatients in RSKDIbu dan Anak Pertiwi Makassar. Methods Observation, questionnaire, interview and document review were the main methods to show the level of satisfaction of outpatients in the hospital. The research questionnaire which given to 97 respondents contained several study aspects of the outpatient satisfaction, namely Reliability, Assurance, Tangibles, Empathy, and Responsiveness. These five aspects were covered in the questionnaire with several indicators whichdirectly reflects the aspects. The results showed that the satisfaction in the reliability, Assurance, Tangibles, Empathy, and Responsiveness aspects were in the satisfactory level. Thesatisfaction result from questionnaire werein line with the results of direct observations and interviews conducted in parallel. Indicators of satisfaction of outpatients in Obstetrics Polyclinic RSKD Ibu and Anak Pertiwi showed a very good level of satisfaction and therefore it needsto be maintainedand improved to keep the performance of the hospital services in a very good level.